Hydration behavior and chloride ingress in cement mortar incorporating a novel core@shell admixture. (April 2022) - Wang, Xuhui; Xu, Jinxia; Guo, Mingzhi
Abstract: A coupled addition of layered double hydroxides (LDHs) (with a high chloride binding capacity) and zeolite (as a pozzolanic material) in concrete is conducive to reducing external chloride ingress. This study aims to evaluate the chloride transport resistance of concrete using a novel Linde type A zeolite (zeolite-LTA)@Mg–Al LDHs (zeolite@LDHs) core@shell material. The effect of the core@shell admixture on cement hydration and chloride penetration into cement mortar were investigated by a comparative experiment. The results showed that the addition of zeolite@LDHs material in cement mortar shortened the setting time, slightly reduced the hytration heat, and exerted a marginal effect on the compressive strength and flexural strength. More importantly, a synergistic effect of LDHs' excellent chloride binding ability and zeolite induced pore refinement remarkably augments the chloride diffusion resistance of the zeolite-LTA@LDHs incorporated cement mortars.